Netralitas Aturan, Ketidaksetaraan Dampak: Diskriminasi Tidak Langsung dan Kesetaraan Pendidikan dalam Tata Kelola Beasiswa Internasional - Abubakar Muhammad jibril; Souad Ezzerouali (Jurnal HAM, 2026)
International scholarship schemes are widely promoted as instruments for advancing educational access and human capital development, particularly in the Global South. Yet their administrative governance frameworks may unintentionally undermine these objectives. This study examines how eligibility requirements and documentation procedures within international scholarship systems shape substantive equality of educational access. Adopting a qualitative socio-legal methodology, the study analyses scholarship policies, administrative regulations, and institutional practices against international human rights standards, particularly Article 13 of the International Covenant on Economic, Social and Cultural Rights and General Comment No. 13 of the Committee on Economic, Social and Cultural Rights. The findings indicate that procedurally uniform requirements, especially those governing documentation timing and administrative compliance, may generate indirectly discriminatory effects by disproportionately disadvantaging academically qualified applicants from structurally under-resourced educational contexts. Such governance practices may further encourage strategic procedural adaptation among applicants, thereby distorting merit-based selection. The study recommends greater procedural flexibility, including conditional admissions mechanisms and context-responsive documentation policies, to better align scholarship administration with substantive equality and the right to education.